Segmenting Indonesian Online Customer - Reny Yuliati (Jurnal InterAct, 2016)
In marketing, internet has developed into a new distribution channel. Moreover, online transactions are growing hugely in recent years. It has created phenomena of online stores, spreading in Indonesia. Competition among online stores become fierce, and marketers should know how consumer behavior in internet environment.   The purpose of this research is to explore the characteristics of each different online consumer and the online store attributes that consumer chose as the important factors in the online store. Based on 203 participants, our findings indicate five segments of the online consumer. Those are online shopping lovers (a group that addicted to buy through the internet), online window shoppers (a group that like to know all the detail information, before they choose to buy), negative judgmental online users (a group who can use internet but do not like online shopping), on off shoppers (a group or segment of people who trust the online store, but prefer to buy directly through offline store)  and  traditional  shoppers  (a  group  of  people  who  don’t  like  online  shopping).  In addition, there is also similarity in those five segments.  Online customers believe that online store attributes, like security and service are important when they want to buy online.